European values : trends and divides over thirty years - Bréchon, Pierre, 1947-; Gonthier, Frédéric. (European Values Studies, 2017)
In sharp contrast to the popular belief that values are converging and becoming increasingly standardized, this book draws on the EVS surveys to show that Europe remains very diverse in terms of values orientations toward the major issues of everyday life. It also addresses how and in what direction values are actually changing, thus emphasizing the joint influence of key factors like secularization, economic development, the rise in educational attainment levels and the welfare state. Written by the team of political scientists and sociologists who are carrying out the EVS surveys in France, this books leads to the striking conclusion that increasingly individualized value systems do not necessarily mirror a more individualistic society.